PERAN MEDIA DALAM PEMBERITAAN TERORISME - Ayu Wardani (JURNAL ILMIAH SYI'AR, 2017)
Terrorism is an action that has been planned by a certain group to conduct acts of terror in various forms of violence to parties that are considered potentially victimized. Media coverage is able to polarize public opinion in response to terrorist acts, whether to be a pros or a cons. Media coverage revolves around radical acts committed by terrorists, anger of victims and families of victims and the implications that arise after the occurrence of acts of terror. Mass media can be a means of supporting acts of terror, such as the news on ideology and the ideals of terrorists can launch terrorist goals in carrying out the action.